Welfare provision by selected self-help organizations : exploratory study - Molefe, Sopeng Prince (University of Limpopo, 1989)
Refer to document
Thesis (PhD. (Social Work)) --University of Limpopo, 1989
Keywords: Welfare organizations; 361.3; Community organisations; Public welfare; Social service